2016
DOI: 10.1111/jfpp.12819
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Natural Food Condiments on Carcinogenic/Mutagenic Heterocyclic Amines Formation in Thermally Processed Camel Meat

Abstract: In the present study, the effect of various natural food condiments (garlic, ginger, pepper, tomato and onion) on the formation of heterocyclic amines (HAs) in cooked camel meat was studied. In control sample, the amount of HAs MeIQx, 4,8‐DiMeIQx and PhIP were obtained between 2.10 and 5.22 ng/g, while, MeIQ and IQ were found less than quantification limit. The camel meat cooked with different food condiments, the HAs were found in lesser amounts. MeIQx, 4,8‐DiMeIQx and PhIP were detected from 0.42 to 2.83 ng/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Thus, it is proven with epidemiologic studies that various chemical compounds form as a result of cooking foods rich in protein, such as cooking meat and fish at high temperatures. All of these compounds are mutagenic and majority of them are also considered as carcinogenic . Among these chemical compounds, heterocyclic aromatic amines (HCAs) have an important place.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is proven with epidemiologic studies that various chemical compounds form as a result of cooking foods rich in protein, such as cooking meat and fish at high temperatures. All of these compounds are mutagenic and majority of them are also considered as carcinogenic . Among these chemical compounds, heterocyclic aromatic amines (HCAs) have an important place.…”
Section: Introductionmentioning
confidence: 99%
“…All of these compounds are mutagenic and majority of them are also considered as carcinogenic. [2][3][4][5][6][7] Among these chemical compounds, heterocyclic aromatic amines (HCAs) have an important place. Firstly, HCAs were discovered by Japanese scientists in 1977, in grilled meat and fish, as a new chemical group.…”
Section: Introductionmentioning
confidence: 99%
“…(2019) demonstrated that ginger (0.5–2.5%) possesses the highest efficiency in inhibiting the formation of both polar and nonpolar HAAs (74–99% and 42–100%) in charcoal grilled lamb patties (10–12 min to attain core temperature of 72°C), followed by cinnamon, Chinese prickly ash, red chili, cumin, and black pepper, with the inhibition efficiency by all the six spices added separately ranging from 46 to 99% for polar HAAs and 31 to 100% for nonpolar HAAs. Similarly, among various spices such as ginger, onion, garlic, red chili, paprika, black pepper, and tomato evaluated for HAAs inhibition efficiency, ginger powder was the most effective in reducing total HAAs content in fried beef and chicken meatballs (180°C) (Lu, Kuhnle, & Cheng, 2018), while tomato and ginger showed a maximum reduction in MeIQx (77 and 69%), 4,5‐DiMeIQx (80 and 71%), and PhIP (79 and 66%) (Khan et al., 2017). Nevertheless, all the spices did show significant reduction in total HAAs content in meat samples.…”
Section: Inhibition Of Spice/herbs On Haas Formationmentioning
confidence: 99%
“…Heterocyclic aromatic amines (HAAs) are known to be mutagenic/carcinogenic substances that result from the cooking of protein‐rich food (Khan et al, 2017). According to the formation process, HAAs can be classified into two groups: aminoimidazoazarenes and aminocarbolines.…”
Section: Introductionmentioning
confidence: 99%